UPAYA MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS MELALUI MODEL RECIPROCAL TEACHING PADA SISWA KELAS VIII SMP NEGERI 10 BANDAR LAMPUNG - Saryantono, Buang; Rahmawati, Fitriana (STKIP PGRI Bandar Lampung, 2019)
This study aims to improve the problem-solving abilities of students of class VIII at SMP Negeri 10 Bandar Lampung, in learning mathematics using the Reciprocal Teaching learning model. This research is a Classroom Action Research (CAR). This action is carried out in 2 cycles where each cycle consists of 4 meetings. At each cycle, students are given a final cycle test to measure their problem solving abilities. Data analysis techniques in this research are descriptive analysis and quantitative analysis. The results showed that learning mathematics using the Reciprocal Teaching learning model can improve problem solving skills. This is indicated by an increase in the average value of the first cycle test of 57.40, while the second cycle test of 73.80. The average percentage of problem solving aspects in cycles I and II are as follows: (a) the ability to understand the problem increases from 50% to 75%, (b) the ability to plan problem solving increases from 62% to 77%, (c) the ability to carry out the plan increased from 59% to 70%, and (d) the ability to interpret the results obtained increased from 61% to 73%.